Distributed Network And Its Security Issues (Trinity Journal of Management, IT & Media (TJMITM), 2014)
It is a situation where a computer programming and the information or  data to be worked on is widely spread over more than one computer,  typically over a network. Prior to economical computer power on the  desktop, computing was actually centralized. Networking and distributed systems provide the infrastructure for computation,  communication and storage involving a heterogeneous and potentially  large number of people, hardware devices, and software processes.  Issues of concern include performance, security, scalability, functionality, and manageability.
Keywords: Computer Programming; Network; Computing; Storage